2020
DOI: 10.1016/j.ecoenv.2020.110446
|View full text |Cite
|
Sign up to set email alerts
|

Impact of temperature on the toxicity of Kraft 36 EC® (a.s. abamectin) and Score 250 EC® (a.s. difenoconazole) to soil organisms under realistic environmental exposure scenarios

Abstract: Impact of temperature on the toxicity of Kraft 36 EC® (a.s. abamectin) and Score 250 EC® (a.s. difenoconazole) to soil organisms under realistic environmental exposure scenarios

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 49 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…In addition, there were no significant differences compared with the CK and SK. Previous studies found that AVM could affect the growth of plants, and it demonstrated that there was the encapsulation effect of γ-CD–MOFs on AVM TC. For the treatment of steam, on the 7th and 14th days, except for M-B, all other treatments had inhibitory effects.…”
Section: Results and Discussionmentioning
confidence: 95%
“…In addition, there were no significant differences compared with the CK and SK. Previous studies found that AVM could affect the growth of plants, and it demonstrated that there was the encapsulation effect of γ-CD–MOFs on AVM TC. For the treatment of steam, on the 7th and 14th days, except for M-B, all other treatments had inhibitory effects.…”
Section: Results and Discussionmentioning
confidence: 95%
“…They aim to eliminate or control pests that harms plants, nematodes, microorganisms, and insects that compete with human food and are responsible for transmitting disease and destroying crops (Brasil, 2002; Instituto Nacional de Câncer José Alencar Gomes da Silva, 2021; Kumar et al, 2021). Brazil is one of the largest agricultural producers, resulting in a high pesticide consumption (i.e., about 20% of global use) (Figueirêdo et al, 2020; Lopes‐Ferreira et al, 2022; Rigotto et al, 2014). However, this intensive use may cause several adverse effects (Moraes, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the wide application and high persistence of DFZ, it can be detected in soil [5], water [6], air [7], and agricultural crops [8]. It was reported that over 1% of soil samples from northern China had DFZ concentrations higher than 0.1 mg/kg [9], the concentration of DFZ in agricultural water in Thailand (Salakru, Nong Sua) was estimated to be 0.028 mg/L, and the concentration of DFZ in air samples from Tanjung Karang was 86.49 ng/m −3 [10].…”
Section: Introductionmentioning
confidence: 99%